Perumusan Strategi Bersaing Pada Laboratorium Klinik Meditest Semarang - Renaldy Prasadana Erickson (Praxis : Jurnal Sains, Teknologi, Masyarakat dan Jejaring, 2021)
Along with the trends of healthy lifestyle in which many people are attentive with their own medical condition, public become more actively check their health. Especially there is Covid-19 pandemic in the present time. Medical check-up can be served by clinical laboratory. This research was performed in Meditest clinical laboratory, located in the city of Semarang. The purpose of this research aims to formulate competitive strategy for Meditest based on definition by Fred R. David. The data used on this research is primary type, gathered by interviewing those responsible to Meditest’s operational activity, such as owner of Meditest, manager, procurement division, marketing division, and lab analyst. Then, the data is processed, beginning from first step using external factor analysis and internal factor analysis, next steps are IE matrix and SWOT matrix, and the final step is QSPM. Result of the research shows that the suitable strategy that can be used by Meditest is market penetration. Marketing and promotion need to be more intense and frequently, especially using popular social media platform so that it makes Meditest to be more known by general public. Also, need to be considered to update several lab equipments that felt dated, replaced with equipments with latest technology, so that those will improve service quality to patients.